2021
DOI: 10.33423/jhetp.v21i8.4501
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Pandemic on Pharmacy Teaching at a Midwestern University

Abstract: and students that the remainder of the semester would be taught using remote learning. The study objective is to determine how the change from the traditional classroom to remote learning impacted students and faculty. Pharmacy students were surveyed to ascertain how the transition to remote learning have impacted their learning. Additionally, faculty were surveyed using a semi-structured interview to assess their instructional efforts. The student survey findings identify several challenges impacting instruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Accordingly, they reported being inquisitive and self-taught when it came to using online teaching tools and pedagogies. This autodidactic drive focused on the discovery, implementation, and evaluation of suitable tools [57,63,69,72,74,91,[94][95][96]. Other studies reported that lecturers swiftly changed their attitudes to overcome reservations towards educational technology and ERT [67,74,94,97].…”
Section: Self-efficacy In Emergency Remote Teachingmentioning
confidence: 99%
“…Accordingly, they reported being inquisitive and self-taught when it came to using online teaching tools and pedagogies. This autodidactic drive focused on the discovery, implementation, and evaluation of suitable tools [57,63,69,72,74,91,[94][95][96]. Other studies reported that lecturers swiftly changed their attitudes to overcome reservations towards educational technology and ERT [67,74,94,97].…”
Section: Self-efficacy In Emergency Remote Teachingmentioning
confidence: 99%
“…1 Major disruption started after a nationwide state of emergency was declared. Lockdown policies were thereafter led by states, 2 during which schools of pharmacy (SOPs) changed their modes of instruction to virtual/online-only or hybrid systems 3,4 to comply with their respective state-level lockdown policies while maintaining accreditation standards. 5 The COVID-19 pandemic also led to an increase and expansion of the clinical roles of pharmacists and changes in experiential education modalities for pharmacy learners.…”
Section: Introductionmentioning
confidence: 99%